Regulation of APD and force by Na+/Ca2+ exchanger in hiPSC-cardiomyocytes. (19th May 2022) - Ismaili, D; Gurr, K; Horvath, A; Yuan, L; Lemoine, MD; Schulz, C; Sani, J; Petersen, J; Reichenspurner, H; Kirchhof, P; Jespersen, T; Eschenhagen, T; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): BMBF Introduction: Human induced pluripotent stem cell-derived cardiomyocytes (HiPSC-CM) are an emerging, powerful tool to study human cardiac physiology, pharmacology and toxicology, to model cardiovascular diseases or even to use for cardiac repair. Understanding the similarities and differences between hiPSC-CM and adult human cardiomyocytes is critical for their use. Here we focus on sodium calcium exchanger (NCX) who plays a crucial role in the Ca2+-homeostasis in the mammalian heart. Importantly, alterations in NCX expression in human heart are associated with various cardiac pathologies such as heart failure or arrhythmias. In order to investigate whether hiPSC-CM could serve as model for adult human heart NCX we measured the properties of NCX in hiPSC-CM and human ventricular tissue. Rat ventricular tissue was used for comparison. Methods: HiPSC-CM were differentiated from a healthy iPSC line and dissociated from engineered heart tissue (EHT). Adult human and rat cardiomyocytes were digested from ventricular samples. We measured NCX current by the whole-cell patch clamp technique at 37 °C. Standard sharp microelectrodes were used to record action potentials (AP). Contractile force in human and rat ventricular samples was measured isometrically. A video-optical contractility test system was used to measure force in EHT. SEA0400 (10 µM) was used to block NCX. Results: NCX currents could be measured in every hiPSC-CM. The NCX current densities in hiPSC-CM were larger than in human ventricular cardiomyocytes (3.2±0.2 pA/pF n=28 vs. 1.3±0.2 pA/pF n=15, p<0.05), but lower than reported for rat left ventricular cardiomyocytes using the same protocol. SEA0400 shortened APD90 markedly in EHT (264.1±24.9 ms to 191±31.6 ms, n=4) and to a lesser extent in rat ventricular tissue (54.4±3.9 ms to 48.9±4.2 ms, n=7). Shortening in human left ventricular preparations was tiny (320±22.1 ms to 305.5±20.3 ms, n=6) and not different from time-matched controls (TMC). Resting membrane potential, action potential amplitude and upstroke velocity were not affected neither in EHT nor in left ventricular preparations (rat and human). Force was significantly increased by NCX block in rat ventricle (by 31±5.4%, n=18) and EHT (by 20.8±3.9%, n=4), but in human left ventricular preparations there was only a tendency to attenuate spontaneous run-down (-3.7±4.3% n=8 with SEA vs. -6.2±3.7% n=12 in TMC). Conclusion: HiPSC-CM possess NCX in the physiological range. HiPSC-CM show NCX-effects on APD and force as predicted from rat ventricle and in full accordance with cardiac physiology. Lack of NCX effect in human adult ventricles that had been already reported previously needs further investigations.